2014
DOI: 10.1039/c4cp00069b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure at nanocontacts of surface passivated CdSe nanorods with gold clusters

Abstract: We report the effects of variation in length on the electronic structure of CdSe nanorods derived from atomic clusters and passivated by fictitious hydrogen atoms. These nanorods are augmented by attaching gold clusters at both the ends to form a nanodumbbell. The goal is to assess the changes at nanolevel after formation of contacts with gold clusters serving as electrodes and compare the results with experimental observations 1 . Calculations involving nanorods of length 4.6Å to 116.6Å are performed using de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Since injection into the SET levels of the Au tip is unlikely to cause bleaching of the NR absorbance, the SET features observed by STS are unlikely to be detectable by spectroelectrochemistry. However, if the MSI states are electronically coupled to the NR conduction band (i.e., tunneling occurs between MSI states and the conduction band), 6,81 then injection into the MSI states will contribute to bleaching of the lowest energy NR absorbance. We therefore posit that bleaching transitions of Au-tipped NRs having an onset near À4.6 eV are due to charge injection into MSI states.…”
Section: Resultsmentioning
confidence: 99%
“…Since injection into the SET levels of the Au tip is unlikely to cause bleaching of the NR absorbance, the SET features observed by STS are unlikely to be detectable by spectroelectrochemistry. However, if the MSI states are electronically coupled to the NR conduction band (i.e., tunneling occurs between MSI states and the conduction band), 6,81 then injection into the MSI states will contribute to bleaching of the lowest energy NR absorbance. We therefore posit that bleaching transitions of Au-tipped NRs having an onset near À4.6 eV are due to charge injection into MSI states.…”
Section: Resultsmentioning
confidence: 99%
“…Monometallic and bimetallic NP have been the subject of intense research efforts from both theoretical and experimental viewpoints, and technological applications in a variety of fields have been envisioned because of the existing simple methods to synthesize functional nanoparticles of commercial importance . It has also been shown that it is feasible to control their physicochemical characteristics for specific purposes, such as in medicine, catalysis, and other industrial applications in the fields of food, and electronics, for example, as nanocontacts in metal‐semiconductor devices …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] It has also been shown that it is feasible to control their physicochemical characteristics for specific purposes, such as in medicine, [8] catalysis, [9] and other industrial applications in the fields of food, [10] and electronics, for example, as nanocontacts in metalsemiconductor devices. [11,12] Structural studies are a recurring topic in current research due to the correlation between the nanoparticle size, shape, and composition, and its physical and chemical properties. The issue of finding the energetically most favorable structures has been addressed through diverse computational techniques, which have led to the discovery of unusual geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Richard A. Vaia and co-authors reported a five times higher fluorescence enhancement by organizing QDs on GNRs, and Anjali Kshirsagar et al reported the electronic structure of free-standing and gold-attached passivated CdSe nanorods [2425]. These studies covered the synthesis of GNR@CdSe/ZnS nanoparticles using different methods; however, most of these synthesis methods are complicated, and it is difficult to reproduce their preparation and desired applications.…”
Section: Introductionmentioning
confidence: 99%